Analysis of the Use of WhatsApp in Food Processing Behavior Changes in Entrepreneurs - RONI GUNAWAN; Dian Maya Sari Siregar; Arifah Devi Fitriani; Muchti Yuda Pratama (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2022)
Background: Food and beverage sanitation hygiene really needs to be guaranteed of its safety, including the sanitation hygiene of home-made snacks produced by food entrepreneurs. Poor food sanitation hygiene can cause food poisoning, which is bad for buyers. Especially during the COVID-19 pandemic, food sanitation hygiene in small and medium businesses must be considered to avoid transmission while maintaining an entrepreneurial image in the midst of the pandemic. Objective: This study aims to analyze behavior changes including knowledge, attitudes, and entrepreneurial actions in food and beverages processing through mentoring using WhatsApp messenger media. Methods: This study used a quasi-experimental approach. The population of this study was small and medium entrepreneurs specializing in food and beverage processing accompanied by an incubator in North Sumatra with as many as 35 entrepreneurs. The samples of this study amounted to 29 food entrepreneurs who were selected using the purposive sampling technique. The time of the study was in July and August 2020. Data were obtained by giving questionnaires before mentoring, two weeks after mentoring, and four weeks after mentoring. The variables consisted of knowledge, attitudes, and actions, as well as assistance to use WhatsApp messenger media. The collected data were then analyzed using the Wilcoxon and Friedman test. Results: The results showed that the mentoring using WhatsApp messenger media could increase knowledge (P value = 0.000), attitudes (P value = 0.000) respondents' actions (P value = 0.015). Conclusion: The role of health workers was very necessary for the use of WhatsApp messenger based social media, including as assistants who present health promotion content, annul negative content, and make positive efforts to reconcile if there be bad communication in the WhatsApp messenger social media group.